Effect of rapid thermal annealing on InP1−xBix grown by molecular beam epitaxy. (7th July 2015) - Wu, X Y; Wang, K; Pan, W W; Wang, P; Li, Y Y; Song, Y X; Gu, Y; Yue, L; Xu, H; Zhang, Z P; Cui, J; Gong, Q; et al.
Abstract: The effect of post-growth rapid thermal annealing on structural and optical properties of InP1−x Bix thin films was investigated. InPBi shows good thermal stability up to 500 °C and a modest improvement in photoluminescence (PL) intensity with an unchanged PL spectral feature. Bismuth outdiffusion from InPBi and strain relaxation are observed at about 600 °C. The InPBi sample annealed at 800 °C shows an unexpected PL spectrum with different energy transitions.